DAYA PREDASI Rhynocoris fuscipes F. (Hemiptera:Reduviidae) TERHADAP ULAT API Setothosea asigna E. (Lepidoptera:Limacodidae) DI LABORATORIUM - Edi Kembaren; Darma Bakti; Lahmuddin Lubis (Universitas Sumatera Utara, 2015)
ABSTRACTThe Ability of Rhynocoris fuscipes F. (Hemiptera: Reduviidae) to nettle caterpillar Setothoseaasigna E. (lepidoptera: limacocidae) as a predator in the laboratory, it was under supervised byProf. Dr. Ir. Darma Bakti, MS. and Ir. Lahmuddin Lubis, MP. The research was to know the abilityof R. fuscipes to Setothosea asigna. The research was held at the Insect Laboratory, Faculty ofAgriculture, University of Sumatera Utara, Medan from April to Juni 2013. It was arranged byCompletely Randomized Design with 6 treatments and four replications, respectively. The total ofpredator againts nettle caterpillar Sethotosea asigna are: R0 (0:8),R1 (2♂:8 ), R2 ( 2♀:8 ) R3,(♂♀:8 ) ,R4 ( 2♂♀:8), R5 (3♂♀:8). The parameters which observed were the mortality persentageof S. asigna caused by predator R. fuscipes and how to consumed. The result showed that the mosteffective treatment is R5, R4, R3, R2, R1 and R0 at a stretch. The matter is shown from the fastest ofability kill of 8 S. asigna that tested is R5 (10 days) and followed by R4, R3, R2, R1, R0.Keywords : Rhynocoris fuscipes F. and Nettle caterpillar setothosea asigna E